The morphology of sella turcica in cleft and non-cleft individuals - Suraj Prasad Sinha; Akhil Shetty; U.S. Krishna Nayak (Elsevier, 2020)
Aims and Objectives: The aim of the study was to analyze the morphology and expedient the linear dimensions of Sella Turcica among cleft and non-cleft Indian individuals, and then to determine whether differences exist between different study groups. Materials and methods: The lateral cephalogram of 300 patients (150 cleft and 150 non-cleft), aged 18 to 30 years who reported for various treatments of malocclusions were studied. Result: The normal morphology of the sella turcica were seen in 85 of the 150 non-cleft individuals which was highest (56.66%) in the non-cleft group, however in the cleft group it was seen in only 16 of the 150 individuals (10.6%). Sella turcica bridge were seen in 10% of the non-cleft subjects, whereas in the cleft group it was seen in 38% of the individuals. A significant difference was seen in the linear measurements of the sella turcica of cleft and no-cleft individuals. Conclusion: The normal morphology of the sella turcica was seen in the majority of the non-cleft individuals. The cleft individuals showed an increased incidence of sella turcica bridging with reduced linear measurements of the sella as compared to the non-cleft individuals. Keywords: Morphology of Sella Turcica, Cleft individuals, Non-cleft individuals